Comparison of the Antifungal Efficacy of EverWild and Citrus Extracts Challenged Against Aspergillus flavus in Semi-Moist Pet Treats - Samuel Kiprotich; Janak Dhakal; Cynthia Rasmussen; Charles G. Aldrich (Kansas Agricultural Experiment Station Research Reports, 2021)
There are increasing requests by pet owners to pet food manufacturers to formulate diets with fewer synthetic additives in favor of more ‘natural’ and sustainably sourced substitutes. Pet owners believe that natural alternatives are healthier and offer longevity to their pets. Therefore, the objective of this study was to investigate and compare the antifungal efficacy of two natural products, fermented whey protein (EverWild; EV) and citrus extract essential oil, when challenged againstAspergillus flavusinoculated in semi-moist pet treats. Semi-moist treats generally contain moisture levels of 20–30%, which is ideal for mold proliferation. The experiment was completely randomized in design. The model and nutritionally complete semi-moist pet treats were produced with three levels of EV (1.0%, 3.0%, and 5.0%), citrus extract (1.0%, 3.0%, and 5.0%), a positive control that contained 0.1% potassium sorbate, or a negative control that contained no treatment. Each treatment was replicated twice and plated in duplicate during fungal analysis. The semi-moist treats were cut into biscuits and inoculated with 0.1 mL aliquots ofAspergillus flavuscultures. Fungal analysis was performed at 0, 3, 6, 9,12, 15, 18, 21, 24, and 28 days. Overall, the survivors ofAspergillus flavuswere reduced over time in all treatments including the negative control. When determining the log reduction from d 0 to 28, the EV included at 1.0%, 3.0%, and 5.0% had a 1.90, 3.89, and 4.58 Log CFU/biscuit reduction while the positive and negative control had 1.19 Log CFU and 0.84 Log CFU/biscuit reduction, respectively. There was a significant difference (P<0.05) in log reduction between EV at 3.0% and 5.0% compared to 1.0% EV, the positive and negative controls, 1.0%, 3.0%, and 5.0% citrus extracts. Citrus extract at 1.0%, 3.0%, and 5.0% had a 1.19, 2.34, and 2.63 Log CFU/biscuit reduction compared to the positive and negative controls (1.19 Log CFU and 0.84 Log CFU/biscuit). In conclusion, a fermented whey protein could be used to inhibit mold growth in semi-moist pet treats.
Keywords: Aspergillus flavus; citrus extract; Everwild; semi-moist treats